PENENTUAN TEMPAT STUDI LANJUT S3 (DOKTORAL) BERDASARKAN KEPUTUSAN INDIVIDUAL DAN KEPUTUSAN KELOMPOK DENGAN MENERAPKAN ANALYTIC HIERARCHY PROCESS (AHP) - Djamilah, Siti (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2009)
The purpose of this research is to determine location of doctoral (S3) study. In choosing a location, this research used multi criterion (multi attribute) decision making that comprised the quality of university, tuition fee and near location. Alternative's university were Gadjah Mada .University, Braw aya University & University of Airlangga. This research tested to lecturer of economic faculty of University of naya Kusuma Surabaya, especially the lecturer of management to make individual decision. Beside that, this research used group decision for choosing location of doctoral study. Questionnaires for group decision were distributed to finanace assistant of rector, head of management and lecturer of management. The analytic hierarchy process (AHP) was used to determine location of doctoral study by individual decision and group decision. Both of individual decision and group decisison had the same result AHP. The result of AHP indicated that Gadjah Mada University was the best alternative to conduct study of doctoral.